Movement Disorders in Cerebral Palsy - Sanger, Terence D. (Journal of Pediatric Neurology, 2015)
Children with cerebral palsy often have a mixture of multiple disorders of movement that interact with each other and with the developmental process. While this complicates the process of symptomatic diagnosis, there is nevertheless a close link between clinical impairments and the underlying etiology and distribution of injury. I describe the major categories of impairment, including hypertonic symptoms, hyperkinetic symptoms, and negative signs. Within each category, there are specific features that are helpful for distinguishing between multiple impairments that affect motor function. Identification of the particular impairments affecting each child is essential to guide appropriate medical and rehabilitation interventions.
Keywords: cerebral palsy; movement disorder; dystonia; athetosis; chorea; hypertonia; hyperkinetic